Key Technology Research on the Rapid-Molding In-Closed Retaining-Wall in Filling Mining - Chaowen Hu; Qian Li; Yilong Wang; Ke Chang; Yongyuan Li; Yaqian Wang; Hui Liu (Shock and Vibration)
Filling mining is a main technology of mining coal resources under buildings, and it has a good effect on preventing ground subsidence. Taking Wangtaipu coal mine of the Shanxi Jincheng Anthracite Coal Mining Group as the engineering background, in order to solve the problem of traditional closed brick wall at the end of working face, which consumes a lot of manpower and material resources, and low efficiency, a technology of rapid-molding in-closed retaining-wall was proposed. Through theoretical analysis and engineering analogy, the overall structure and size of the mold bag were designed. Through the experiment of high-water bleeding rate and slurry expansion, it was determined that the best water-cement ratio was 0.85 : 1, and the best additive content was 25 kg/m3. Taking economic factors into consideration, it was determined that liquid sodium silicate was used as the admixture. The XV2308 working face was selected for on-site testing and the on-site monitoring of the roof pressure, the roadway deformation, and the stress of the coal body. The results showed that there was no large area roof pressure on the working face, the coal body was under stable force, the stress concentration coefficient was small, the coal pillar had no plastic failure, and the roadway deformation was small. Through on-site monitoring of ground subsidence, the results showed that the amount of ground movement and deformation were small. The maximum value of subsidence was 12 mm, which could meet the requirements of safety production and had significant economic benefits.